Reconsidering Forced Labels: Outcomes of Sexual Assault Survivors Versus Victims (and Those Who Choose Neither). (May 2018) - Williamson, Jessica; Serna, Kelly
The goal of the current study was to assess the effects of self-labeling on attitudes related to victim- and self-blaming and self-compassion outcomes in 85 participants (75 women, 10 men) who have experienced sexual assault. Participants classified themselves as either a survivor, victim, or neither survivor nor victim of sexual assault. Regardless of self-classification, groups did not differ in victim-blaming (rape myth acceptance), self-blaming, or levels of self-compassion. Implications for language and forced labels of those who have experienced sexual assault are discussed.